Independent Care of Family Medicinal Plants and Acupressure for Blood Pressure in Hypertension - Hermin, Catur (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Hypertension that occurs in the long term and is not treated will affect all organ systems of the body so that various complications occur that can cause death. To prevent complications in hypertension, hypertension control efforts are needed, one of which is complementary therapy in the form of utilizing toga and acupressure. Family medicinal plants or “TOGA” can be processed into various types of preparations so that they can be consumed by the community as a natural medicine to replace chemical drugs. The purpose of this study was to analyze the effect of the asman toga and acupressure program on blood pressure before and after being given asman toga and acupressure. This type of research is a one group pre-post test with a quasi-experimental research design. The number of samples in this study was 40 respondents. The research instrument used a needle tensiometer, questionnaire, “Asman Toga” pocket book and register book. The results of this study based on the results of the Wilcoxon Signed Rank Test statistical test on the pre-test and post-test obtained a p-value of 0.000 or <0.05, then Ho was rejected and Ha was accepted, which means that there is an effect in providing the “Asman toga” and acupressure program where there was a decrease in blood pressure. It is hoped that the results of this study can utilize toga and acupressure to maintain health because toga and acupressure are health facilities that are easy to apply.